Highly parallel bending tests for fungal hyphae enabled by two-photon polymerization of microfluidic mold - Brinkmann, Steffen; Schrader, Marcel; Meinen, Sven; Kampen, Ingo; Kwade, Arno; Dietzel, Andreas (Frontiers in Bioengineering and Biotechnology, 2024)
Filamentous microorganisms exhibit a complex macro-morphology constituted of branched and cross-linked hyphae. Fully resolved mechanical models of such mycelial compounds rely heavily on accurate input data for mechanical properties of individual hyphae. Due to their irregular shape and high adaptability to environmental factors, the measurement of these intrinsic properties remains challenging. To overcome previous shortcomings of microfluidic bending tests, a novel system for the precise measurement of the individual bending stiffness of fungal hyphae is presented in this study. Utilizing two-photon polymerization, microfluidic molds were fabricated with a multi-material approach, enabling the creation of 3D cell traps for spore immobilization. Unlike previous works applying the methodology of microfluidic bending tests, the hyphae were deflected in the vertical center of the microfluidic channel, eliminating the adverse influence of nearby walls on measurements. This lead to a significant increase in measurement yield compared to the conventional design. The accuracy and reproducibility of bending tests was ensured through validation of the measurement flow using micro-particle image velocimetry. Our results revealed that the bending stiffness of hyphae of Aspergillus niger is approximately three to four times higher than that reported for Candida albicans hyphae. At the same time, the derived longitudinal Young's Modulus of the hyphal cell wall yields a comparable value for both organisms. The methodology established in this study provides a powerful tool for studying the effects of cultivation conditions on the intrinsic mechanical properties of single hyphae. Applying the results to resolved numerical models of mycelial compounds promises to shed light on their response to hydrodynamic stresses in biotechnological cultivation, which influences their expressed macro-morphology and in turn, product yields.